Trialling computer touch-screen technology to assess psychological distress in patients with gynaecological cancer - Halkett, Georgia; Jiwa, Moyez; Tanner, P.; Fournier, Celine; Katris, P. (Australasian Medical Journal Pty Ltd, 2010)
Background - Cancer impacts on the psychological well-being of many cancer patients. Appropriate tools can be used to assist health professionals in identifying patient needs and psychological distress. Recent research suggests that touch-screen technology can be used to administer surveys. The aim of this study was to evaluate the use of a touch-screen system in comparison to written questionnaires in a large tertiary hospital in Western Australia (WA). Method - Patients who were scheduled to commence treatment for gynaecological cancer participated in this study. Patients were assigned to complete either a written questionnaire or the same survey using the touch-screen technology. Both survey methods contained the same scales. All participants were asked to complete a follow-up patient satisfaction survey. Semi-structured interviews were conducted with health professionals to elicit views about the implementation of the technology and the available referral pathways. Data were analysed using descriptive statistics and content analysis.Results - Thirty patients completed the touch-screen questionnaires and an equal number completed the survey on paper. Participants who used the touch-screen technology were not significantly more satisfied than other participants. Four themes were noted in the interviews with health professionals: usability of technology, patients’ acceptance of technology, advantages of psychological screening and the value of the instruments included. Conclusion - Although previous studies report that computerised assessments are a feasible option for assessing cancer patients’ needs, the data collected in this study demonstrates that the technology was not reliable with significant practical problems. The technology did not serve patients better than pen and paper.